Donor and recipient risk factor analysis of inferior postheart transplantation outcome in the era of durable mechanical assist devices - Urban, Marian; Booth, Karen; Schueler, Stephan; Netuka, Ivan; MacGowan, Guy (Clinical transplantation, 2018)
The study objective is to quantify the impact of donor and recipient variables on heart transplant survival in recipients with a significant proportion of implanted continuous-flow left ventricular assist devices (LVADs). This is a prospective cohort study of International Society for Heart and Lung Transplantation (ISHLT) Registry that includes all primary heart-alone transplants in adult recipients (January 2005 and June 2013, N = 15 532, 27% LVADs). Donor and recipient characteristics were assessed for association with death or graft failure within 90 days and between 90 days and 5 years after transplantation. On Cox proportional hazard model donor cause of death other than head trauma (hazard ratio [HR] 1.985, P < 0.0001), recipient congenital (HR 2.7555, P < 0.0001) and ischemic (HR 1.165, P = 0.0383) vs dilated etiology and female donor heart transplanted into male recipient (HR 1.207, P = 0.0354) were predictors of death or graft failure within 90 days. Between 90 days and 5 years, donor cigarette use (HR 1.232, P = 0.0001), recipient cigarette use (HR 1.193, P = 0.0003), diabetes (HR 1.159, P = 0.0050), arterial hypertension (HR 1.129, P = 0.0115), and ischemic vs dilative cardiomyopathy had an increased probability of death or graft failure.
Keywords: Young Adult; Heart Transplantation; příjemce transplantátu; Heart-Assist Devices; hodnocení rizik; Male; Postoperative Complications; Graft Survival; Risk Assessment; Risk Factors; Survival Rate; mladý dospělý; následné studie; prognóza; Adult; Tissue Donors; Transplant Recipients; Prospective Studies; dospělí; mužské pohlaví; pooperační komplikace; Graft Rejection; dárci tkání; faktorová analýza statistická; transplantace srdce; Follow-Up Studies; Factor Analysis, Statistical; lidé; ženské pohlaví; Humans; rejekce štěpu; přežívání štěpu; rizikové faktory; podpůrné srdeční systémy; Prognosis; Female; lidé středního věku; míra přežití; Middle Aged; prospektivní studie